A study on the antibiotic resistance of Shigella - Pramita G Dwipoerwantoro; Sri P Pulungsih; Nuraini I Susanti; Hartaniah Sadikin; Agus Firmansyah (Indonesian Pediatric Society, 2005)
Background The hospital morbidity caused by Shigella or dysen-tery ranges between 0.3 to 2.9%. Irrational use of antibiotics causesa persistent diarrhea and may lead to drug resistance.Objectives With various kinds of antibiotics available in Indone-sia at the moment, this study aimed to anticipate the kinds of anti-biotics appropriate for shigellosis and to evaluate the clinical spec-trum of dysentery in children in Indonesia.Method The study involved 50 children diagnosed with dysenteryor dysentery-like syndrome, aged 1 to 12 years, who came to fourdifferent hospitals in Jakarta, from November 2001 to April 2002.Parents were asked for their consent. Interviewers recorded de-tails of the children’s history of illness and the physical examina-tions. Stool culture and resistance tests were done.Results Fifty dysentery cases, comprising 30 males and 20 fe-males, 98% aged from 1 to 5 years, came to the four hospitalsduring the study period. Only 24 cases had positive Shigella cul-tures, of which 87% were Shigella flexneri and 17% were Shigellasonnei. The clinical manifestations of shigellosis were bloody stools(83%), mucus in the stool (75%), and watery diarrhea (96%). Fe-ver and tenesmus were absent in 67% and 92% of subjects, re-spectively. Almost 87% of shigellosis cases were resistant tocotrimoxazole; all were sensitive to colistin and most were sensi-tive to nalidixic acid.Conclusion This data suggests that colistin and nalidixic acid aredrugs of choice for dysentery syndrome. The clinical manifesta-tion of dysentery is not always accompanied by bloody stools butmostly incorporates watery diarrhea and mucus in the stool